Direct Speech-Language Intervention Effects on Augmentative and Alternative Communication System Use in Adults With Developmental Disabilities in a Naturalistic Environment. - Hughes, Deanna M.; Vento-Wilson, Margaret; Boyd, LouAnne E. (American Journal of Speech-Language Pathology, 2022)
Purpose: Research involving the effects of augmentative and alternative communication (AAC) intervention in adults, especially in naturalistic settings, has been identified as a critical public health need. Despite rapid advances in hightech AAC, many adults with developmental disabilities have experienced reduced access to assistive technology and AAC, which can function as a de facto environmental barrier to participation, for these individuals. As a means of decreasing barriers to participation, this study targeted skill increases in the operational, linguistic, social, and strategic use of AAC systems. Method: This study used a preexperimental, single-case AB design to identify skill level changes in the operational, linguistic, social, and strategic use of their AAC system from baseline to the completion of intervention. The four adult participants with developmental disabilities and limited use of natural speech as a primary modality of communication were identified through a collaborative relationship between a communication sciences and disorder university program and a state-run adult day program for individuals who had aged out of the K-12 school system. Each participant received direct intervention in the four areas described across 7 weeks. Results: Visual analysis and percent of nonoverlap of all pairs were used to identify changes in performance occurring between baseline and the conclusion of the intervention period. Results revealed increases across the specific skills, with individuals' variation across participants and target area. Out of 22 total goals targeted, strong effect sizes were observed for 10 goals and moderate effect sizes were observed for seven. Conclusions: Skill increases in the four areas of AAC system use can be achieved with direct intervention in adults with developmental disabilities and limited use of natural speech as a primary modality of communication. This approach also underscores the value of collaborations between university training programs, providers of adult services, and adult participants as a costeffective strategy for service delivery.